The importance of bioindication in water ecotoxicology - Sadowska, Urszula (Studia Ecologiae et Bioethicae, 2012)
Bioindication methods are applied in ecotoxicological studies which in turn are widely used in the biological monitoring of surface water. Bioindication has been applied for a long time and so far it has created multiple classifications based on diagnosis groups of organisms. Bioindicators play a signi]cant role in bioindication; they are species used to monitor the health of the environment or ecosystem. Some of them are standard test organisms used in ecotoxicology in the so-called bioassays, which provide a great deal of information about the type and in^uence of pollution. These studies are vital nowadays, as compounds have been found to be the greatest threat to aquatic ecosystems. In relation to ecotoxicology, research allows us to determine bioconcentration, bioaccumulation and biomagni]cation factors, and to assess the ecological status of water used in many different indexes so as to determine such relevant parameters as saprobic, biological bio-diversity and biotic indexes. Poland is preparing for the extension of monitoring systems that take into account all the necessary elements of the environment, even the sediments. It is required by the Water Frame Directive.